International comparative explorations of prostitution policies: lessons from two European projects. Issue 2 (3rd April 2018) - Crowhurst, Isabel; Skilbrei, May-Len
Abstract : In this contribution we reflect on our experiences of co-designing and coordinating two comparative projects on prostitution policies in Europe by focusing in particular on the epistemological workings underpinning their design and execution. We set out two main goals. The first is to shed light on what the epistemological and methodological issues we encountered reveal about the field of prostitution policy studies, an endeavor which can contribute to better comparative research in the field. The second goal is to relate the scope, developments, outcomes and expectations of the two projects to recent attempts to identify a "one-size-fits-all" model of prostitution regulation, and to interrogate whether transplanting it across Europe is a desirable outcome. Building on the lessons learned from the projects, we propose an approach to prostitution policy development that is reflective of the specific contexts within which the policies are meant to be applied.